CLINICAL TRIAL ASSESSING THE PREVALENCE OF ORAL COMPLICATION IN A DENTURE WEARERS POPULATION - Cosmin Bida; Doriana Agop-Forna; Dana Gabriela Budala; Norina Forna (Romanian Journal of Oral Rehabilitation)
Material and Methods: This study investigates the prevalence of loco-regional complications and craniomandibular disorders in partially edentulous patients, with a focus on the relationship between age and these complications. The results highlight the external pterygoid muscles as the most frequently affected, with a prevalence of pain or tenderness in 69.2% of subjects, aligning with previous studies. Results: Parafunctional habits, such as bruxism, were also identified as predominant factors contributing to craniomandibular dysfunction. Audible TMJ noises, including cracking (30.4%) and crepitation (25.9%), were observed, but these do not necessarily indicate degenerative disorders; rather, they are linked to functional issues, such as a lack of coordination of the condylar meniscus. Discussions: A significant relationship between aging and increased prevalence of craniomandibular disorders was confirmed, with elderly patients showing higher instances of degenerative changes, including osteoarthritis and decreased muscle tone. Psychological factors related to tooth loss and aging further complicate the presentation of these disorders. Conclusions: The findings emphasize the importance of personalized treatment approaches that consider both physiological and psychological aspects.Future research should focus on longitudinal studies to explore the progression of craniomandibular disorders, particularly in elderly and partially edentulous populations, to improve diagnosis and management strategies.